A modelling analysis of financial incentives for hepatitis C testing and treatment uptake delivered through a community‐based testing campaign. Issue 11 (28th August 2021) - Palmer, Anna Y.; Chan, Kico; Gold, Judy; Layton, Chloe; Elsum, Imogen; Hellard, Margaret; Stoove, Mark; Doyle, Joseph S.; Pedrana, Alisa; Scott, Nick; ,
Abstract: Financial incentives may reduce opportunity costs associated with people who become lost to follow‐up in hepatitis C treatment programs. We estimated the impact that different financial incentive amounts would need to have on retention in care to maintain the same unit cost per (1) RNA‐positive person completing testing (defined as awareness of RNA status) and (2) RNA diagnosed person initiating treatment. Costing data were obtained from a 2019 community‐based testing campaign focused on engaging people who inject drugs. For different financial incentive amounts, we modelled the corresponding improvements in retention in care that would be needed to maintain the same overall (1) unit cost per testing completion and (2) unit cost per treatment initiation. In the testing campaign, the unit cost per RNA‐positive person completing testing was A3215 and the unit cost per RNA diagnosed person initiating treatment was A1055. Modelling found that an incentive of A500 per RNA‐positive person completing testing would result in more people completing testing for the same unit cost if the percentage of attendees receiving their test results increased from 63% to 74%. An incentive of A200 per RNA diagnosed person initiating treatment would result in more people initiating treatment for the same unit cost if the percentage initiating treatment increased from 67% to 83%. Monetary incentives for completing testing and initiating treatment may be an effective way to increase retention in care without increasing the overall unit cost of completing testing/initiating treatment.